Unpacking communication strategies in casual conversation: An exploration of Indonesian EFL learners - Susilowati, Endang; Kusumaningtyas, Etika Dewi (English Education and Literature Journal (E-Jou), 2025)
Engaging in casual conversation is essential for EFL learners, as it enhances fluency, boosts confidence, and provides authentic language practice. However, Indonesian learners often face challenges in managing spontaneous interactions effectively, leading them to employ various strategies to manage communication breakdowns. This study aims to explore the communication strategies used by Indonesian EFL learners and examine the factors influencing their strategic choices. This study involved third-semester English education students and adopted a descriptive qualitative method with conversational analysis. Data were collected through audio-video recordings and interviews and analyzed based on Celce-Murcia et al.’s (1995) framework of communication strategies. The findings reveal that learners utilized all five main types and fourteen sub-types of communication strategies. Stalling or time-gaining strategies are the most frequently used, followed by achievement strategies or compensatory strategies, interactional strategies, self-monitoring strategies, and avoidance or reduction strategies. The frequent sub-types employed include fillers, hesitation devices, and gambits; self and other repetition; code-switching; and meaning negotiation strategies. Conversely, strategies such as message replacement, topic avoidance, all-purpose words, word coinage, and foreignizing were not employed. In addition, learners’ strategic choices were influenced by factors such as limited vocabulary and language proficiency, cognitive processing needs, the desire to convey meaning, efforts to ensure mutual understanding, self-awareness of errors, and topic complexity. Finally, this study offers some pedagogical implications for the betterment of EFL teaching and learning